Evaluation of the Relationship Between Midpalatal Suture Maturation Indicators as Predictors for Surgically-Assisted and Conventional Rapid Maxillary Expansion - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2021)
Rapid maxillary expansion (RME) is an effective orthopedic procedure to correct maxillary transversal deficiency in young patients. In cases of sutural closure, surgically assisted RME is used to reduce the resistance to sutural disjunction. Foundation of a diagnostic relationship between maturation indices and the expected skeletal response to expansion can enable clinicians to identify the need for surgically assisted RME prospectively. The primary aim of this study was to assess the correlation between the amount of achieved skeletal expansion with midpalatal suture density on computed tomography images, and the secondary aim was to assess the correlation between the amount of achieved skeletal expansion with the recently suggested midpalatal suture maturation indicators: cervical vertebral maturation (CVS), midpalatal suture maturation stage (MPSM) and midpalatal suture density ratio. Forty Digital Imaging and Communications in Medicine data from the archived computed tomography scans of 20 patients (mean age: 15.55 years) before RME (T-1) and after 3-month retention period (T-2) were analyzed. The tested maturity indicators did not show statistically significant correlation between the skeletal effect proportions. However, clinically and radiologically effective RME was seen in MPSMs A, B, and C and also cervical vertebra stages CVS5 and CVS6. More research is needed to determine a diagnostic predictor for the skeletal effects of maxillary expansion treatment modalities.
Keywords: Computed tomography; maxillary constriction; midpalatal suture; suture density; PALATAL SUTURE; GROWTH